The effects of commercially available footwear on foot pain and disability in people with gout: a pilot study - Rome, Keith (BioMed Central, 2013)
BACKGROUND: There is limited evidence on non-pharmacological interventions for gout. The aim of the study was to determine whether a footwear intervention can reduce foot pain and musculoskeletal disability in people with gout. METHODS: Thirty-six people with gout participated in a prospective intervention study over 8 weeks. Participants selected one of 4 pairs of shoes and thereafter wore the shoes for 8 weeks. The primary outcome was foot pain using a 100 mm visual analogue scale. Secondary outcomes related to function and disability were also analysed. RESULTS: The Cardio Zip shoe was selected by 58% of participants. Compared with baseline, overall scores for all shoes at 8-weeks demonstrated a decrease in foot pain (p = 0.03), general pain (p = 0.012), Health Assessment Questionnaire (HAQ)-II (p = 0.016) and Leeds Foot Impact Scale (LFIS) impairment subscale (p = 0.03). No significant differences were observed in other patient reported outcomes including patient global assessment, LFIS activity subscale, and Lower Limb Task Questionnaire subscales (all p > 0.10). We observed significant improvements between baseline measurements using the participants’ own shoes and the Cardio Zip for foot pain (p = 0.002), general pain (p = 0.001), HAQ-II (p = 0.002) and LFIS impairment subscale (p = 0.004) after 8 weeks. The other three shoes did not improve pain or disability. CONCLUSIONS: Footwear with good cushioning, and motion control may reduce foot pain and disability in people with gout.